Design of a Vibrotactile Vest for Contour Perception - Wu, Juan; Zhang, Jun; Yan, Ju; Liu, Wei; Song, Guangming (International journal of advanced robotic systems, 2012)
A vibrotactile array is a promising human computer interface which could display graphical information to users in a tactile form. This paper presents the design and testing of an image contour display system with a vibrotactile array. The tactile image display system is attached to the back of the user. It converts visual graphics into 2D tactile images and allows subjects to feel the contours of objects through vibration stimulus. The system consists of a USB camera, 48 (6×8) vibrating motors and an embedded control system. The image is captured by the camera and the 2D contour is extracted and transformed into vibrotactile stimuli using a temporal-spatial dynamic coding method. Preliminary experiments were carried out and the optimal parameters of the vibrating time and duration were explored. To evaluate the feasibility and robustness of this vibration mode, letters were also tactilely displayed and the recognition rate about the alphabet letter display was investigated. It was shown that under the condition of no pre-training for the subjects, the recognition rate was 82%. Such a recognition rate is higher than that of the scanning mode (47.5%) and the improved handwriting mode (76.8%). The results indicated that the proposed method was efficient in conveying the contour information to the visually impaired by means of vibrations.